A new integrative approach combining right heart catheterization and echocardiography to stage aortic stenosis-related cardiac damage - Viva, Tommaso; Postolache, Adriana; Nguyen Trung, Mai-Linh; Danthine, Pauline; Petitjean, Hélène; Bruno, Vito Domenico; Martinez, Christophe; Lempereur, Mathieu; Guazzi, Marco; Aghezzaf, Samy; Coisne, Augustin; Oury, Cécile; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Although staging of the extent of AS-related cardiac damages is usually performed via echocardiography, this technique has considerable limitations in assessing pulmonary artery and right chambers pressures. The present hypothesis generating study sought to explore the efficacy of a staging system of cardiac damage based on echocardiographic and invasive (right heart catheterization (RHC)) hemodynamic parameters in patients undergoing transcatheter aortic valve implantation (TAVI). Methods: We studied 90 symptomatic patients with severe AS in whom echocardiographic and invasive evaluation by RHC was obtained prior to TAVI. Cardiac damage stages were defined as follows: no cardiac damage (Stage 0), left ventricular (LV) damage (Stage 1), left atrial or mitral valve damage (Stage 2), pulmonary vasculature or tricuspid valve damage (Stage 3), and right ventricular (RV) dysfunction or low-flow state (Stage 4). With the integrative approach using RHC, pulmonary hypertension (PH) was defined as a mPAP 25 mmHg and the low-flow state corresponded to a cardiac index <1.8 L/min/m 2 and a right atrial pressure >10 mmHg. Results: During follow-up (median: 2.9 years), 43 patients (47.8%) died. The integrative cardiac damage staging was associated with a significant increase in all-cause and cardiovascular mortality per each increase of cardiac damage stage, whereas the outcome was similar according to the echocardiographic staging. Conclusions: A staging system of cardiac lesion based on echocardiographic and invasive hemodynamic parameters in patients with severe AS undergoing TAVI predicts mortality. Patients with pre-existing PH,  moderate tricuspid regurgitation and/or RV dysfunction and a low-flow state had a markedly increased risk of death. Further larger studies are needed to validate our findings.